2016
DOI: 10.1007/s11187-016-9736-7
|View full text |Cite
|
Sign up to set email alerts
|

Institutional drivers of high-growth firms: country-level evidence from 26 transition economies

Abstract: High-growth firms (HCF) represent a highly desirable subset of firms, which provide disproportionate economic gains, and greater insight into their determinants which is of interest to policymakers, scholars and business owners. We contribute to the literature on HGFs, which is largely absent of cross-national institutional studies, by examining the institutional conditions driving HGFs in 26 transition countries over a long period comprising three panels between 1998 and 2009. Using an institutional hierarchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
137
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 139 publications
(196 reference statements)
5
137
0
Order By: Relevance
“…complementing) or undermining (i.e. substituting) informal institutions Tonoyan, Strohmeyer, and Habib 2010;Krasniqi and Desai 2016;Hashi and Krasniqi 2011). Informal institutions can complement formal institutions if they create incentives to comply with the formal institutions, thereby addressing problems of social interaction and coordination and enhancing the efficiency of formal institutions (Baumol 1990;North 1990).…”
Section: Explaining Unregistered Employment: Theoretical Framing and mentioning
confidence: 99%
See 1 more Smart Citation
“…complementing) or undermining (i.e. substituting) informal institutions Tonoyan, Strohmeyer, and Habib 2010;Krasniqi and Desai 2016;Hashi and Krasniqi 2011). Informal institutions can complement formal institutions if they create incentives to comply with the formal institutions, thereby addressing problems of social interaction and coordination and enhancing the efficiency of formal institutions (Baumol 1990;North 1990).…”
Section: Explaining Unregistered Employment: Theoretical Framing and mentioning
confidence: 99%
“…including the influence of tax morale (as a proxy indicator of the degree of institutional asymmetry), which is becoming a very popular strand in recent research (Krasniqi and Desai 2016;Williams and Krasniqi 2017, Williams and Martínez 2014, Williams and Horodnic 2017b.…”
Section: Data and Variables 31 Data And Samplementioning
confidence: 99%
“…The aforementioned determinants, both demand and supply side, are relevant for all countries, however, in transitioning economies, their impact on growth and sometimes the vector of a business's development is determined by the features of the institutional environment. The body of empirical research on SME performance in developing economies found a robust relationship between firm performance and the quality of institutions [Aidis et al, 2008;Molz et al, 2009;Blagojevic, Damijan, 2013;Sharafutdinova, Kisunko, 2014;Yukhanaev et al, 2015;Volchek et al, 2013a,b;Wang, You, 2012;Krasniki, Desai, 2016;Welter, Smallbone, 2011]. However, the mechanism behind their interactions remains poorly studied.…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%
“…Economies that did not manage to develop according to the Western model must operate under an alternative informal institutional network [Smallbone, Welter, 2010], which is prone to rent-seeking, shadow schemes and similarly, tends to incentivize sub-optimal behavior among firms [Golikova, Ermilova, 2006;Sharafutdinova, Kisunko, 2014]. As a result, a discussion of a firm's aspirations for growth, scale of production and performance in transitioning economies without recourse to a study of institutional issues is liable to be incomplete [Aidis et al, 2008;Aidis, 2015;Welter, Smallbone, 2011;Smallbone et al, 2014;Krasniki, Desai, 2016;Wang, You, 2012]. Moreover, an institution-based study has become the main theoretical framework for business research on emerging economies and researchers tend to explore the interplay of formal and informal institutions at multiple levels of analysis [Thorsten et al, 2005;Meyer, Peng, 2005Estrin et al, 2013].…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%
“…The aforementioned determinants, both demand and supply side, are relevant for all countries, however, in transitioning economies, their impact on growth and sometimes the vector of a business's development is determined by the features of the institutional environment. The body of empirical research on SME performance in developing economies found a robust relationship between firm performance and the quality of institutions Molz et al, 2009;Blagojevic, Damijan, 2013;Sharafutdinova, Kisunko, 2014;Yukhanaev et al, 2015;Volchek et al, 2013a,b;Wang, You, 2012;Krasniki, Desai, 2016;. However, the mechanism behind their interactions remains poorly studied.…”
Section: Determinants and Patterns Of Sme Growth: The Russian Contextmentioning
confidence: 99%